Rock Magnetic Cyclostratigraphy of the Carboniferous Mauch Chunk Formation, Pottsville, PA, United States - Kodama, Kenneth P. (Frontiers in Earth Science, 2019)
A rock magnetic cyclostratigraphy study was conducted on the Carboniferous Mauch Chunk Formation red beds at Pottsville, Pennsylvania to determine if Milankovitch climate forcing could be detected in these terrestrial, fluvial deposits with hematite as the predominant ferromagnetic mineral. This locality was chosen because a robust magnetostratigraphy had already been established for it thus giving an estimate of its sediment accumulation rate. Magnetic susceptibility was measured in the laboratory with a KLY-3s Kappabridge on samples collected every 0.5 m of section for 68 m of section. Magnetic susceptibility measurements were also made in the field using an SM-20 portable susceptibility meter. The time series that resulted were different but yielded very similar power spectra calculated by the multi-taper method. Significant spectral peaks isolated by robust red noise and harmonic f-tests yielded peaks identified to be short eccentricity (125 ka and 95 ka), obliquity (35 ka) and precession (21 and 17.5 ka) in the Carboniferous. Average spectral misfit analysis of these peaks for both the Kappabridge and SM-20 time series gave the identical sediment accumulation rate of 5.69 cm/ka, somewhat slower than the ~9 cm/ka average rate for >250 m of section estimated from magnetostratigraphy and biostratigraphic correlation throughout northeastern North America. Analysis of the low temperature magnetic susceptibility versus temperature curves for a 10 m stratigraphic interval of samples indicates that the ferromagnetic content of the bulk susceptibility appears to be driving the precession- and obliquity-scale bulk susceptibility variations. This observation suggests that climate change in the source area causes more or less erosion of ferromagnetic minerals that are then deposited into a background of paramagnetic clays or diamagnetic quartz sand in the depositional basin. Our study clearly shows that fluvial terrestrial sediments can record astronomically-forced climate change. Our study also indicates that portable susceptibility measurements are a valid way of collecting reconnaissance rock magnetic time series to determine sampling intervals for more detailed studies.